Editorial: Care for a Human Being - Błasiak, Anna; Pasierbek, Wit (Horyzonty Wychowania, 2020)
The main aims of our journal are to offer interdisciplinary reflection on man, to show new horizons of human life, and to search for the truth about a human being. This issue of the Horizons of Education entitled “Care for a human being” is in line with these aims. The topics addressed in the articles concern care and caring for others and possible ways of supporting contemporary man. Care comes straight from the essence of man, his vocation, and the set of values he holds. Taking care of another person is intended to protect him against danger and is linked to tending to him and his affairs. In this form, it becomes a source of human development for the carer and adds something valuable to his meaning of life and the social and cultural progress. The more numerous and greater the dangers in the world are, the more relevant care for others, but also for oneself, becomes. It is possible to analyse the notion of care in relation either to those to whom it is addressed or to those who offer their care to others. A person who is cared for primarily experiences the feeling that his needs are satisfied and that he is supported, also in the emotional sphere, which is conductive to his development and the formation of a positive attitude towards the world and other people. Those who show concern for others are active subjects who undertake targeted actions for the benefit of those in need, and – at the same time – develop their empathy and kindness and eliminate hostility, anger, and envy. Taking care of others increases carers’ self-acceptance and satisfaction, their sense of agency and being needed, they gain a positive image of the world, of themselves, and of others, and they intensify their sense of the meaning of life. Thus, it can be claimed that people who participate in the relationship of care become empowered not only in their emotional and spiritual spheres but also motivational and intellectual ones, as they acquire new knowledge…